The effect of cold pack nursing therapy on reducing pain levels in the close-fracture Pertrochanteric Femur in the Emergency Room of Klungkung Regency Hospital. - Yunita, Kadek; Sanjana, I Wayan Edi; Sukadana, I Gede (Babali Emergency and Disaster Research, 2024)
Background: Fractures will experience pain, which is an unpleasant multidimensional experience due to tissue damage. One of the non-pharmacological therapies that can be given to patients with Pertrochanteric Femur Fractures is the Cold Pack technique (cold compress), which effectively reduces pain in mild orthopaedic cases, while in severe orthopaedic cases, using ice water immersion is more recommended. Research Objective: To determine the effect of cold pack nursing therapy on reducing pain levels in the close-fracture Pertrochanteric Femur in the Emergency Room of Klungkung Regency Hospital. Methods: Methods using a case study approach. The sample in this study amounted to two people selected by the purposive sampling technique. Results: Providing cold compress action with cold packs to reduce pain in patients who have closed fractures obtained the results of the patient saying there is a change that is felt, namely slightly reduced pain in the fracture area in patients with Pertrochanteric femur fractures in the emergency room of Klungkung Hospital. Conclusions: Giving cold pack therapy can effectively reduce pain intensity in patients with closed fractures and decrease the pain scale after getting cold pack therapy nursing interventions.